FRI0597 Near-Infrared Spectroscopic Hand Imaging: A New Tool to Assess Microcirculatory Impairment in Systemic Sclerosis. (9th June 2015) - Gargani, L.; Barskova, T.; Hartwig, V.; Marinelli, M.; Guiducci, S.; Bellando Randone, S.; Blagojevic, J.; Matucci Cerinic, M.
Abstract : Background: Patients affected by systemic sclerosis (SSc) develop functional and structural microcirculatory dysfunction, which leads to skin fibrosis initially affecting distal extremity. Recent studies have tested the possibility of evaluating the skin microcirculation of the entire hand and its spatial heterogeneity by means of optical Near-Infrared Spectroscopic (NIRS) of blood HbO2 saturation (stO2 ). The NIRS-sensitive camera is a non-invasive tissue oxygenation measurement system based on near infrared light. The camera reports and approximates value of stO2 in superficial tissue. Processing software of the NIRS-camera generates 2D imaging maps automatically in real time. Objectives: To test whether NIRS hand imaging may evaluate microcirculatory dysfunction in SSc Methods: Forty-two SSc patients (90% women, mean age 55.1±15.6 years) and 18 sex and age-matched healthy controls (86% women, mean age 54.3±14.5 years, p=.89) underwent evaluation of the hand microcirculation by NIRS 2D imaging. A blood pressure cuff was applied to the forearm and 3-min ischemia was induced. Images were acquired at basal conditions at each 10 seconds during 3 minutes of ischemia and during reperfusion condition. Four regions of interest (ROI) were positioned on each fingertip, from the second to the fifth finger. Results: A significant difference was found between controls and SSc in basal stO2 (84.4±9.9 vs 75.9±12.5%, p<.01), minimum stO2 (65.6±10.2 vs 54.4±10.9%, p<.001), maximum stO2 (92.4±3.9 vs 86.8±6.6%, p<.001), time to maximum stO2 (247±42 vs 277±60 msec, p<.05). Patients with anti-topoisomerase positivity had lower values of basal stO2 compared to patients without (78.8±11.7 vs 69.3±12.7, p<.05). No significant differences were found among different degrees of impairment at nailfold capillaroscopy (early, active, late). Conclusions: Data show that NIRS hand imaging is a simple, automated promising tool to non-invasively assess the skin microcirculation of the entire hand, which can complement information deriving from nailfold capillaroscopy. Acknowledgements: We thank Mr. Gennaro D'Angelo for his technical support. Disclosure of Interest: None declared